The Academic Achievement of Senior High School Students in Yogyakarta Viewed from the Influence of Their Time Management - Lathifah Irsyadiyah Husna; Hanif Cahyo Adi Kistoro (Insight School Academy, 2026)
Introduction to the Problem: Learning achievement is a proof of the learning process undertaken bystudents. In the process of attaining learning achievement, several factors exert influence, both internal and external to the student. One internal factor is time management, namely a person’s skill in managing time and understanding its obstacles so that goals are achieved effectively. Purpose: This study aims to determine the influence of time management on the learning achievement of tenth-grade students at SMA Negeri 2 Bantul in the 2023/2024 academic year. Design/Methods/Approach: This study used a quantitative research design. It was conducted at SMA Negeri 2 Bantul, taking a sample of 181 students from a total population of 266 tenth-grade students, drawn through probability sampling with a simple random sampling technique. The independent variable was time management (X), while the dependent variable was learning achievement in the Islamic Education subject. The analysis technique used was a nonparametric test with the aid of SPSS 23 software. Findings: The results show a positive and significant influence of time management on the learning achievement of tenth-grade students, as Ha was accepted at a 95% confidence level with a significance value of 0.012 < 0.05. The magnitude of the influence of time management on learning achievement in Islamic Education did not contribute greatly, as shown by the r-square value of 0.186. This means the level of influence of time management is 18.6%, and the remainder is influenced by variables outside this study.